2020
DOI: 10.1167/jov.20.4.13
|View full text |Cite
|
Sign up to set email alerts
|

Effects of light map orientation and shape on the visual perception of canonical materials

Abstract: We previously presented a systematic optics-based canonical approach to test material-lighting interactions in their full natural ecology, combining canonical material and lighting modes. Analyzing the power of the spherical harmonics components of the lighting allowed us to predict the lighting effects on material perception for generic natural illumination environments. To further understand how material properties can be brought out or communicated visually, in the current study, we tested whether and how l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 47 publications
2
14
0
Order By: Relevance
“…A correct estimation of roughness seems to be especially difficult for homogeneous illuminations, even if they are real-world illuminations. More important than the realism of the mirrored scene seems to be the statistical nature of the illumination map, in particular the number and distribution of light sources (Dror, Willsky, & Adelson, 2004;Pont & te Pas, 2006;Zhang et al, 2019, Zhang, de Ridder, Barla, & Pont, 2020. Zhang et al (2019) distinguish in the direction of decreasing homogeneity the three canonical illumination categories ambient, focus, and brilliance, and found in their Experiment 2 that the gloss rating of a highly glossy material decreased with increasing illumination homogeneity.…”
Section: Comparison With Previous Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A correct estimation of roughness seems to be especially difficult for homogeneous illuminations, even if they are real-world illuminations. More important than the realism of the mirrored scene seems to be the statistical nature of the illumination map, in particular the number and distribution of light sources (Dror, Willsky, & Adelson, 2004;Pont & te Pas, 2006;Zhang et al, 2019, Zhang, de Ridder, Barla, & Pont, 2020. Zhang et al (2019) distinguish in the direction of decreasing homogeneity the three canonical illumination categories ambient, focus, and brilliance, and found in their Experiment 2 that the gloss rating of a highly glossy material decreased with increasing illumination homogeneity.…”
Section: Comparison With Previous Resultsmentioning
confidence: 99%
“…A correct estimation of roughness seems to be especially difficult for homogeneous illuminations, even if they are real-world illuminations. More important than the realism of the mirrored scene seems to be the statistical nature of the illumination map, in particular the number and distribution of light sources ( Dror, Willsky, & Adelson, 2004 ; Pont & te Pas, 2006 ; Zhang et al., 2019 , Zhang, de Ridder, Barla, & Pont, 2020 ).…”
Section: Experiment: Constancy Of Perceived Roughnessmentioning
confidence: 99%
See 1 more Smart Citation
“…This early observation suggested that a perceptually uniform color space would be a complex mathematical entity, and these complexities were not fully GLOSS SCALING AND DISCRIMINABILITY appreciated until the next century, when it was discovered that small differences in chromaticity could only be adequately specified within local regions of the CIE 1931 color space (MacAdam, 1943;Smith & Guild, 1931). Similarly, the prospect of a uniform perceptual space for surface gloss remains elusive because changes in illumination, shape, and viewpoint can drastically alter the perception of surface material properties (Fleming et al, 2003;Ho, Maloney, & Landy, 2007;Norman, Todd, & Phillips, 2020;Vangorp, Laurijssen, & Dutré, 2007;Zhang, de Ridder, Barla, & Pont, 2020), which therefore means that the validity of any gloss space will be constrained by the viewing conditions chosen for its construction (Fores, Fairchild, & Tastl, 2014). Despite these difficulties, our finding that MLDS provides a solution for both scaling and discriminability of gloss indicates that the construction of a perceptually uniform gloss space is a tractable problem.…”
Section: Discussionmentioning
confidence: 99%
“…This early observation suggested that a perceptually uniform color space would be a complex mathematical entity, and these complexities were not fully GLOSS SCALING AND DISCRIMINABILITY appreciated until the next century, when it was discovered that small differences in chromaticity could only be adequately specified within local regions of the CIE 1931 color space (MacAdam, 1943;Smith & Guild, 1931). Similarly, the prospect of a uniform perceptual space for surface gloss remains elusive because changes in illumination, shape, and viewpoint can drastically alter the perception of surface material properties (Fleming et al, 2003;Ho, Maloney, & Landy, 2007;Norman, Todd, & Phillips, 2020;Vangorp, Laurijssen, & Dutré, 2007;Zhang, de Ridder, Barla, & Pont, 2020), which therefore means that the validity of any gloss space will be constrained by the viewing conditions chosen for its construction (Fores, Fairchild, & Tastl, 2014). Despite these difficulties, our finding that MLDS provides a solution for both scaling and discriminability of gloss indicates that the construction of a perceptually uniform gloss space is a tractable problem.…”
Section: Discussionmentioning
confidence: 99%